Work Stress Impact towards Employee Performances - Evelin, Kennie; Siemin Ciamas, Elserra (Adpebi Science Series, 2022)
In this study, the author wanted to identify the problem of “Does work stress affect employee performance at Kakiku Cemara Asri Medan?” The aim is to determine the effect of work stress on employee performance at Kakiku Cemara Asri Medan. The author uses associative quantative research methods. Associative research is a research method where the relationship that occurs is causal, work stress is an unavoidable part of human life and can occur at any time in every human being which can affect many things, one of which is employee performance. The data collection technique used by the author in this research is to use a questionnaire. The sample used by the author in this study were all 31 employees of Kakiku Cemara Asri Medan. The instrument used in this research is the validity and reliability test. Based on calculations carried out with the SPSS version 26 application program, it turns out that the correlation result is 0.687 and the value of sig. deviation from linearity is 0.276 which indicates that there is a linear relationship between work stress and employee performance. From the results of r square of 47.2% and the rest is influenced by other factors that were not tested in this study. From the calculation of the regression analysis, the regression equation Y = 13.816 + 0.819X is obtained. Therefore, it can be concluded that work stress affects employee performance at Kakiku Cemara Asri Medan.